Repeated social defeat stress differently affects arthritis-associated hypersensitivity in male and female mice - La Porta, Carmen; Plum, Thomas; Palme, Rupert; Mack, Matthias; Tappe-Theodor, Anke (Brain, behavior and immunity, 2024)
Chronic stress enhances the risk of neuropsychiatric disorders and contributes to the aggravation and chronicity of pain. The development of stress-associated diseases, including pain, is affected by individual vulnerability or resilience to stress, although the mechanisms remain elusive. We used the repeated social defeat stress model promoting susceptible and resilient phenotypes in male and female mice and induced knee mono-arthritis to investigate the impact of stress vulnerability on pain and immune system regulation. We analyzed different pain-related behaviors, measured blood cytokine and immune cell levels, and performed histological analyses at the knee joints and pain/stress-related brain areas. Stress susceptible male and female mice showed prolonged arthritis-associated hypersensitivity. Interestingly, hypersensitivity was exacerbated in male but not female mice. In males, stress promoted transiently increased neutrophils and Ly6Chigh monocytes, lasting longer in susceptible than resilient mice. While resilient male mice displayed persistently increased levels of the anti-inflammatory interleukin (IL)-10, susceptible mice showed increased levels of the pro-inflammatory IL-6 at the early- and IL-12 at the late arthritis stage. Although joint inflammation levels were comparable among groups, macrophage and neutrophil infiltration was higher in the synovium of susceptible mice. Notably, only susceptible male mice, but not females, presented microgliosis and monocyte infiltration in the prefrontal cortex at the late arthritis stage. Blood Ly6Chigh monocyte depletion during the early inflammatory phase abrogated late-stage hypersensitivity and the associated histological alterations in susceptible male mice. Thus, recruitment of blood Ly6Chigh monocytes during the early arthritis phase might be a key factor mediating the persistence of arthritis pain in susceptible male mice. Alternative neuro-immune pathways that remain to be explored might be involved in females.